2021
DOI: 10.1101/2021.02.06.430041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subgenomic RNAs as molecular indicators of asymptomatic SARS-CoV-2 infection

Abstract: In coronaviridae such as SARS-CoV-2, subgenomic RNAs (sgRNA) are replicative intermediates, therefore, their abundance and structures could infer viral replication activity and severity of host infection. Here, we systematically characterized the sgRNA expression and their structural variation in 81 clinical specimens collected from symptomatic and asymptomatic individuals with a goal of assessing viral genomic signatures of disease severity. We demonstrated the highly coordinated and consistent expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…To date, previous studies reported evidence regarding the detection of viral sgRNAs using sequencing, RT-PCR and ddPCR, and all these findings were based on non-vaccinated cases [ 8 , 23 , 24 ]. The detection of viral sgRNA coupled with an increased viral load has been shown to be indicative of an aggravation of the disease [ 11 ]. Conversely, a reduction in viral load combined with a decrease in sgRNA might reflect a reduced risk of transmission to other susceptible contacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, previous studies reported evidence regarding the detection of viral sgRNAs using sequencing, RT-PCR and ddPCR, and all these findings were based on non-vaccinated cases [ 8 , 23 , 24 ]. The detection of viral sgRNA coupled with an increased viral load has been shown to be indicative of an aggravation of the disease [ 11 ]. Conversely, a reduction in viral load combined with a decrease in sgRNA might reflect a reduced risk of transmission to other susceptible contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rapid and accurate detection of SARS-CoV-2, as well as of viral infectivity, are essential in controlling the outbreak of infections [ 6 ]. Based on the literature, the detection of SARS-CoV-2 subgenomic RNA (sgRNA) in diagnostic samples can indicate active virus replication/transcription and recent infection [ 6 , 7 , 8 , 9 , 10 , 11 ]. Indeed, in the Coronaviridae family, including SARS-CoV-2, sgRNAs are replicative intermediates, and their abundance may reflect viral replication activity and the severity of host infection.…”
Section: Introductionmentioning
confidence: 99%
“…SgmRNAs can be considered markers of ongoing active viral replication and, likely, of viral infectivity, as they are synthesized exclusively inside infected cells and not packaged into virions 20,34,35 . Although our data are not related to clinical data and/or to infectiousness data on cell culture, we believe that this study provides evidence for the application of ddPCR and meta-transcriptomics for the study of the SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports regarding the clinical utility of using the presence of sgRNA as a predictor of infectivity. Some studies promote its use [10, 11] while others (including those using the Wölfel-sgE primer-probe set) deemed it unsuitable for predicting the presence of infectious virus [5, 13, 14]. However, the presence of sgRNA has been used to successfully distinguish input challenge virus from actively replicating virus, particularly in non-human primate models of SARS-CoV-2 vaccination and challenge [15-19].…”
Section: Introductionmentioning
confidence: 99%